Effects of Agricultural Applications on CO2 Emission and Ways to Reduce - Caner Yerli; Üstün Şahin; Talip Çakmakcı; Şefik Tüfenkçi (Turkish Journal of Agriculture: Food Science and Technology)
Global warming, which has been increasing in recent years, is due to the increasing amount of greenhouse gases in the atmosphere. The agricultural sector, which has a 25% share in greenhouse gas formation, plays an important role in global warming. CO2, which has a share of 82% among greenhouse gases, is shown as the most important greenhouse gas. It is estimated that 10% of the CO2 in the atmosphere is missioned from the soil. When soil organic carbon, which is an indicator of soil fertility, is released into the atmosphere as CO2, N and S compound gases return to the earth and it causes inefficient soil as well as global warming. Organic carbon is a source of CO2 emissions when the soil is mismanaged. The organic carbon in the soil is transformed into CO2 with loosening of the soil and accumulates in the atmosphere, after it exposure to temperature and oxygen. Unconscious tillage and irrigations increase the physical and biological activity of the soil and cause CO2 emissions from the soil. CO2 emission, which is the main cause of drought, needs to be reduced with low cost, easy and practical applications. At the beginning of these applications, can be listed reduced tillage, deficit irrigation, reduction of fertilizer usage, reuse of agricultural wastes and agricultural management of wastewater. In this review, it is aimed to investigate CO2 emission effect of soil tillage depth and tools, exhaust gases of the vehicles used in soil tillage, the amount of irrigation water and irrigation methods, deficit irrigation, irrigation with wastewater, precipitation, plant factor, fertilization, properties and temperature of soil. In addition, approaches that can be applied to reduce CO2 emission are mentioned.